(4 intermediate revisions by one other user not shown)
Line 1: Line 1:
 
We are given the input to an LTI system along with the system's impulse response and told to find the output y(t).  Since the input and impulse response are given, we simply use convolution on x(t) and h(t) to find the system's output.
 
We are given the input to an LTI system along with the system's impulse response and told to find the output y(t).  Since the input and impulse response are given, we simply use convolution on x(t) and h(t) to find the system's output.
  
<math>y(t) = h(t) * x(t) = \int_{-\infty}^\infty h(\tau)x(t - \tau)d(\tau)</math>
+
<math>y(t) = h(t) * x(t) = \int_{-\infty}^\infty h(\tau)x(t-\tau)d\tau</math>
 +
 
  
 
Plugging in the given x(t) and h(t) values results in:
 
Plugging in the given x(t) and h(t) values results in:
  
<math>y(t) = \int_{-\infty}^\infty e^{-\tau}u(\tau)u(t - \tau - 1)d(\tau)</math>
+
<math>
 +
\begin{align}
 +
y(t) & = \int_{-\infty}^\infty e^{-\tau}u(\tau)u(t-\tau-1)d\tau \\
 +
      & = \int_0^\infty e^{-\tau}u(t-\tau-1)d\tau \\
 +
      & = \int_0^{t-1} e^{-\tau}d\tau  \\
 +
      & = 1-e^{-(t-1)}\, \mbox{ for } t > 1
 +
\end{align}
 +
</math>
  
:<math>= \int_0^\infty e^{-\tau}u(t - \tau - 1)d(\tau)</math>
 
  
:<math>= \int_0^{t-1} e^{-\tau}d(\tau)</math>
+
Since x(t) = 0 when t < 1:
  
:<math>= 1 - e^{-(t - 1)}\,</math> for t > 1
+
<math>y(t) = 0\, \mbox{ for } t < 1</math>
  
 +
 +
<math>\therefore y(t) =
 +
\begin{cases}
 +
  1-e^{-(t-1)},  & \mbox{if }t\mbox{ is} > 1 \\
 +
  0, & \mbox{if }t\mbox{ is} < 1
 +
\end{cases}</math>
  
Since x(t) = 0 when t < 1:
+
==Alternative Solutions==
 +
[[Problem 5 - Alternate Solution_OldKiwi]]
  
<math>y(t) = 0\,</math> for t < 1
+
[[Problem 5 - Graphical Solution_OldKiwi]]

Latest revision as of 16:23, 3 July 2008

We are given the input to an LTI system along with the system's impulse response and told to find the output y(t). Since the input and impulse response are given, we simply use convolution on x(t) and h(t) to find the system's output.

$ y(t) = h(t) * x(t) = \int_{-\infty}^\infty h(\tau)x(t-\tau)d\tau $


Plugging in the given x(t) and h(t) values results in:

$ \begin{align} y(t) & = \int_{-\infty}^\infty e^{-\tau}u(\tau)u(t-\tau-1)d\tau \\ & = \int_0^\infty e^{-\tau}u(t-\tau-1)d\tau \\ & = \int_0^{t-1} e^{-\tau}d\tau \\ & = 1-e^{-(t-1)}\, \mbox{ for } t > 1 \end{align} $


Since x(t) = 0 when t < 1:

$ y(t) = 0\, \mbox{ for } t < 1 $


$ \therefore y(t) = \begin{cases} 1-e^{-(t-1)}, & \mbox{if }t\mbox{ is} > 1 \\ 0, & \mbox{if }t\mbox{ is} < 1 \end{cases} $

Alternative Solutions

Problem 5 - Alternate Solution_OldKiwi

Problem 5 - Graphical Solution_OldKiwi

Alumni Liaison

Prof. Math. Ohio State and Associate Dean
Outstanding Alumnus Purdue Math 2008

Jeff McNeal